2015
DOI: 10.2495/cmem-v3-n4-340-349
|View full text |Cite
|
Sign up to set email alerts
|

DFT and X-RAY study of structural, electronic, elastic and optical properties in Be1–XZnXS alloys depending on vegard’s law

Abstract: Structural, optical and electronic properties and elastic constants of Be 1-x Zn x S alloys have been studied by employing the commercial code Castep based on density functional theory. The generalized gradient approximation and local density approximation were utilized as exchange correlation. Using elastic constants for compounds, bulk modulus, band gap, Fermi energy and Kramers-Kronig relations, dielectric constants and the refractive index have been found through calculations. Apart from these, X-ray measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 25 publications
3
3
0
Order By: Relevance
“…The bulk modulus computed in the present work is less than all three other calculations. The elastic constants c 12 and c 44 computed in this work using PBE-GGA are in good agreement with the values computed by Glutekin et al [19], while the c 11 shows some deviation.…”
Section: Structural Propertiessupporting
confidence: 89%
See 4 more Smart Citations
“…The bulk modulus computed in the present work is less than all three other calculations. The elastic constants c 12 and c 44 computed in this work using PBE-GGA are in good agreement with the values computed by Glutekin et al [19], while the c 11 shows some deviation.…”
Section: Structural Propertiessupporting
confidence: 89%
“…We found that both the PBE-GGA and PZ-LDA approaches predict direct bandgap for Be 0.75 Zn 0.25 S. However, the value of the bandgap predicted by PZ-LDA (2.86 eV) is lower than PBE-GGA (3.21 eV), inconsistent with the usual bandgap underestimation by LDA calculations than PBE. The computed bandgaps at Γ and X points of symmetry using PBE-GGA are in agreement with the previous calculations applying the PW-PP and FP-LAPW methods [19,20]; a small deviation is found with FP-LMTO results predicting bandgaps of 2.94 eV and 3.97 eV at Γ and X points. By calculating bowing parameters, Baziz et al [20] predicted a direct-to-indirect bandgap transition from Γ to X at x=0.76.…”
Section: Electronic and Optical Propertiessupporting
confidence: 89%
See 3 more Smart Citations